Modulating multi-hole reaction pathways for photoelectrochemical water oxidation on gold nanocatalysts. Issue 5 (8th April 2020) - Zhang, Yuchao; Zhang, Yunlu; Guo, Wenxiao; Johnston-Peck, Aaron C.; Hu, Yue; Song, Xuening; Wei, Wei David
Abstract : Catechol stabilizes photo-generated holes on metal nanoparticles to create a new multi-hole reaction pathway for oxidizing water under visible light. Abstract : Natural photosynthesis utilizes a redox cascade consisting of enzymes and molecular mediators that trap and stabilize hot carriers to achieve efficient multiple charge transfer. In this aspect, great challenges are facing artificial photochemistry regarding the extremely short lifetimes of photo-generated hot carriers. Herein, using Au nanoparticle photocatalysts as a model, we report that photoelectrodeposited catechol molecules on Au/TiO2 heterostructures trap and stabilize photo-generated hot holes on Au and further introduce a new multi-hole reaction pathway in which those long-lived catechol-trapped holes cooperate with newly generated holes on Au. The new mechanism boosts photoelectrochemical water oxidation on Au by one order of magnitude. Our study illustrates a strategy to integrate metal nanoparticles, semiconductors, and molecular redox mediators to effectively separate charge carriers and harvest hot holes for driving photochemical reactions.